Zirconium in the Nuclear Industry: Eleventh International Symposium 1996
DOI: 10.1520/stp16168s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing Temperature on Corrosion Behavior and ZrO2 Microstructure of Zircaloy-4 Cladding Tube

Abstract: This paper describes the corrosion behavior and the ZrO2 microstructure of Zircaloy-4 (Zry-4) cladding tubes that were intermediate annealed at various temperatures. The corrosion behavior of the cladding tubes was studied by autoclave tests performed under 633 K water condition and 673 K steam condition. A TEM examination shows that the microstructure of ZrO2 formed on the Zry-4 matrix consisted of both the columnar structure and the equiaxed grain. The grain size of the columnar grain was approximately 30 by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Many researchers have attempted to identify the relationships between the corrosion behaviors and the oxide microstructures, thereby proposing that a columnar structure enhanced the corrosion resistance while an equiaxed struc- ture did not [6,16,23,24]. In order to determine the variation of oxide microstructure, TEM studies were performed on corroded samples having a thin oxide formed at pre-transition in water, as shown in Fig.…”
Section: Oxide Characteristicsmentioning
confidence: 99%
“…Many researchers have attempted to identify the relationships between the corrosion behaviors and the oxide microstructures, thereby proposing that a columnar structure enhanced the corrosion resistance while an equiaxed struc- ture did not [6,16,23,24]. In order to determine the variation of oxide microstructure, TEM studies were performed on corroded samples having a thin oxide formed at pre-transition in water, as shown in Fig.…”
Section: Oxide Characteristicsmentioning
confidence: 99%
“…It was suggested that the grain boundary diffusion of the oxygen ion was accelerated by the transformation of the ZrO 2 microstructure from the large columnar grain to the fine equiaxed grain. The equiaxed grain was dominantly observed around the precipitate that was incorporated into the ZrO 2 oxide and the transformation of the ZrO 2 microstructure might be caused dominantly by oxidation of the intermetallic precipitates [15]. The present study showed that the effect of precipitate size was more responsible for the difference in corrosion behavior between Al and A2 alloys.…”
Section: Discussionmentioning
confidence: 51%
“…Oxide characteristics such as oxide morphology and precipitates incorporated into the oxide are known to play an important role in the oxidation process of Zircaloys. It was shown that the equiaxed grain to columnar grain volume ratio in ZrO 2 oxide increased with increasing weight gain, especially after the first transition [15]. It was suggested that the grain boundary diffusion of the oxygen ion was accelerated by the transformation of the ZrO 2 microstructure from the large columnar grain to the fine equiaxed grain.…”
Section: Discussionmentioning
confidence: 99%